Evidence of weaker phenotypic plasticity by prey to novel cues from non‐native predators. Issue 15 (2nd July 2016) - Hollander, Johan; Bourdeau, Paul E.
Abstract: A central question in evolutionary biology is how coevolutionary history between predator and prey influences their interactions. Contemporary global change and range expansion of exotic organisms impose a great challenge for prey species, which are increasingly exposed to invading non‐native predators, with which they share no evolutionary history. Here, we complete a comprehensive survey of empirical studies of coevolved and naive predator−prey interactions to assess whether a shared evolutionary history with predators influences the magnitude of predator‐induced defenses mounted by prey. Using marine bivalves and gastropods as model prey, we found that coevolved prey and predator‐naive prey showed large discrepancies in magnitude of predator‐induced phenotypic plasticity. Although naive prey, predominantly among bivalve species, did exhibit some level of plasticity – prey exposed to native predators showed significantly larger amounts of phenotypic plasticity. We discuss these results and the implications they may have for native communities and ecosystems. Abstract : Understanding how naive interactions develop and evolve is crucial in order to predict how global changes might affect indigenous species. However, because of differences in the way novel predators induce defenses in prey, a general consensus is missing on how naive prey exposed to novel predator coevolve. For that reason, this study is unique and timely since it takes a broader perspective by combining a large number of studies in order to identify general patterns and test theoretical predictions about the interface of predator−prey co‐evolution and phenotypic plasticity.